Kontrol Overheating Elemen Pemanas Menggunakan PLC, HMI, dan Modul GSM - Hery Wahyudi; Kusmadi Kusmadi (LPPM Universitas Sangga Buana, 2025)
This research focuses on designing and implementing a monitoring and control system for the ZYD-20 steam turbine lubricating oil purification machine at PT Borneo Alumina Indonesia, Mempawah, West Borneo. The system aims to prevent overheating of the heater element, which could damage the equipment and reduce oil quality. It employs a 3-wire RTD PT100 sensor for real-time temperature monitoring, a PLC to process sensor data and control protective actions (shutting down the inlet pump, outlet pump, vacuum pump, and cutting off power to the heater), and an HMI to display temperature data, operational status, and overheating alarms. Additionally, an Arduino Uno with a GSM module sends SMS notifications to the supervisor during an emergency stop triggered by overheating. This system enhances operational stability, minimizes overheating risks, preserves lubricating oil quality, and improves both efficiency and safety of the purification process.